Olfactory neuroblastoma: a rare sinonasal malignancy - Uppal, Athar Adnan; Zaman, Saira; Shahbaz, Ayesha; Iram, Sadia (Journal of the Pakistan Medical Association, 2024)
Olfactory neuroblastoma is a rare malignant tumour arising from the olfactory nerve and extending into the nasal cavity. In this case report, the case of a 42-year-old male is presented. The patient had a two-month history of progressive nasal blockage and episodes of epistaxis. No complaint of anosmia or facial pain was reported. All the necessary examinations were performed. Upon investigation, the CT scan and MRI showed a polypoid mass involving the right maxillary sinus, eroding the medial wall and expanding into the osteo-meatal complex. The diagnosis of olfactory neuroblastoma was confirmed through histopathological examination and further validated by immunohistochemistry as it was positive for synaptophysin, chromogranin, gamma enolase, and neurofilament. On staging, the tumour was Kadish B. The mass was excised by lateral rhinotomy. The patient was kept on radiotherapy and was free from recurrence upon follow-up 10 months later. ---Continue